Review Article: Concept of Srotorodha (Blockage of Channels) in Relation to Aam - Sajwan, Neha; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2022)
One of the main reasons of disease is an aggravated dosha. These intensified doshas become lodged in channels, resulting in abnormalities or channel obstruction, which leads to a variety of illnesses. Blockage of channels is another key cause of disease, in addition to improper digestive fire and suppression of desire. The tissue elements or constituents undergoing change are transported to their destination via circulatory pathways. The term "channel" refers to the system of circulation. Contaminated diet and regimen are the cause of body and mind channel obstruction. The function and quality of the dependent tissues are disrupted or reduced when the channel is blocked. Increased flow of contents, obstruction, and the formation of nodules in the channels, as well as flow diversion, are all signs of abnormal channels. Blockage of channels might involve obstruction and the appearance of nodules in the channels. Metabolism is a continual process that occurs in our bodies. The natural activity of the body produces free radicals during such metabolic changes, which are damaging to our bodies in the long run. They are the ones who make us old and start the ageing process, in which the body’s physical and mental functions deteriorate. It is related to Aam in Ayurvedic terminology, which is the result of incorrect digestion and this aam has the potential to block channels and disrupt their operation.